Determination of the optimal parameters of power distribution networks by the method of criterion analysis - A D Taslimov, A A Alimov, M V Melikuziev, F M Rakhimov (International Journal of Advanced Science and Technology, 2020)
In article the values of a complex of optimum parameters and laws of their formation taking intoaccount all influencing restrictions by a method of the criterion analysis are defined, on the basis of iteconomic feasibility of application of the limited number of sections of cables of city distributivenetworks is proved. By means of the given method the analysis of influence of technical restrictions oneconomic expediency of optimized parameters is spent and practical recommendations on use of thereceived optimum parameters for city distributive electric networks are generated.